2020
DOI: 10.1016/j.yebeh.2020.107100
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram alterations associated with psychiatric disorders in temporal lobe epilepsy with mesial sclerosis: A systematic review

Abstract: Temporal lobe epilepsy (TLE) is the most frequent focal epilepsy in adults and has been associated with psychiatric disorders (PD), especially the TLE with mesial temporal sclerosis (MTS). Electroencephalogram (EEG) could help in locating the epileptogenic zone and supply information regarding cerebral electric activity in these patients. However, there is a scarcity of knowledge about the association between EEG findings and comorbid PD in TLE. The objective of this review was to proceed a systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Finally, the diversity be-tween patients is even more important when considering comorbidities (i.e. conditions co-occurring with seizures), such as cognitive deficits, anxiety, and depression (Holmes, 2015, Krishnan, 2020, de Barros Lourenço et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the diversity be-tween patients is even more important when considering comorbidities (i.e. conditions co-occurring with seizures), such as cognitive deficits, anxiety, and depression (Holmes, 2015, Krishnan, 2020, de Barros Lourenço et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A large variability also exists in hypometabolism in patients with TLE ( Guedj et al, 2015 ). Finally, the diversity between patients is even more important when considering comorbidities (i.e., conditions co-occurring with seizures), such as cognitive deficits, anxiety, and depression ( Holmes, 2015 ; de Barros Lourenço et al, 2020 ; Krishnan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mesial temporal sclerosis (MTS) is the most common structural abnormality associated with TLE. MTS is correlated to a higher prevalence of psychiatric symptoms up to 70% in pharmacoresistant forms of TLE ( 11 ). The aim of this review is to analyze the psychiatric comorbidity of TLE and identify actual management and therapeutic perspectives that might increase the quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most controversial issues regarding the association between TLE and psychiatric comorbidities refers to electroencephalographic characteristics of this association. In a recent meta-analysis on the subject (Lourenço et al, 2020), the authors concluded that there are few published studies, with contradictory conclusions regarding the laterality and rate of epileptiform discharges, as well as the psychiatric pathologies found (psychosis × depression). Bragatti et al (2009) found an association between epileptiform discharges occurring in the left hemisphere with a three times greater chance of mood disorders, and, when infrequent (<1/min), these were statistically associated with mood disorders (Bragatti et al, 2014).…”
Section: Eeg and Psychiatric Disorders In Temporal Lobe Epilepsymentioning
confidence: 99%